Innovative processing of films and nanocrystalline powders - Choy, Kwang-Leong (Imperial College Press, 2002)
The use of advanced engineering ceramic films and powders for structural and functional applications is expanding rapidly. Improved materials and innovative methods of fabrication are needed to enhance the engineering performance and reduce the production costs. This book highlights innovative/cost-effective material-processing methods, at a mature production stage and also in development. In addition, issues and strategies associated with scaling-up are emphasized.
Keywords: Nanostructured materials -- Congresses.; Electronic ceramics -- Congresses.; Thin films -- Congresses.; Powders -- Congresses.; elektronické knihy; electronic books